(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: The prevalence of hypertension is still high and a research about new intervention is needed to preventing pregnancy and labour complication that could caused by hypertension. Soaking foot in warm water and paling classical music are contemporary relaxan intervension. The combination of these therapy expected to optimally reducing blood pressure. Dayaknese classical music has been chosen as a utilization of local culture. Objective: To analyze the effectiveness of soaking foor in warm water and playing classical music on pregnant women with hypertension at PMB Prima Kuala Kapuas. Methods: This research classified as pre experimental with pretest-posttest group design to 16 pregnant women that has been chosen with total sampling technique. Data analized univariately in frequency distribution table and bivariately using Wilcoxon test. Results: All of the respondent were hypertensive before getting therapy as 16 of 16 respondents (100%). Majority of respondent were not hypertensive after getting therapy as 14 of 16 respondents (87,5%). Hypothesis test showed that p value = 0,000 < 0,05 which means there is an effectiveness of the therapy in pregnant women with hypertension. Conclusion: Combination of soaking foor in warm water and playing classical music can reducing the blood pressure on pregnant women with hypertension.